Development and validation of the Arabic children’s strong communication scale: a pilot study - Alhamami, Munassir; Alduais, Ahmed; Alasmari, Muhammad; Qasem, Fawaz (Frontiers in Psychology, 2024)
The assessment of communication skills in Arabic-speaking children has been challenged by a lack of culturally and linguistically appropriate tools. The Arabic Children's Strong Communication Scale (ACSCS) was developed in response to this need, adapting the Children's Communication Checklist-2 (CCC-2) to better suit the Arabic context.Aims: This study aimed to validate the ACSCS and establish its utility in measuring communication strengths among Arabic-speaking children.Methods: A total of 102 participants completed the questionnaire, which included relatives, teachers, and speech therapists of children aged 4-16. Twenty-two items were developed that targeted children communication strengths. The items were based on a theoretical framework that encompassed language proficiency, social communication, and behavioral aspects.Exploratory Factor Analysis (EFA) and Confirmatory Composite Analysis (CCA) were employed to validate the structure of the ACSCS. The scale's reliability was tested using Cronbach's alpha and composite reliability, while its validity was assessed through convergent and discriminant validity measures.The EFA and CCA confirmed a clear distinction of communication strengths.Reliability analyses indicated high internal consistency for the ACSCS. Discriminant validity was established, showing that the ACSCS accurately measures distinct facets of communication skills.The ACSCS is a valid and reliable instrument for assessing communication skills in Arabic-speaking children, reflecting strengths across various domains.The scale has significant implications for educational and clinical settings, providing a culturally sensitive tool for practitioners and researchers to assess and support the communication development of Arabic-speaking children.